Comparison of prophylactic ankle cloth wrapping and taping on vertical jump height in division I football players - Henderson, J.; Lyons, B. C.; Tucker, S.; Davidson, B. (International Journal of Athletic Therapy & Training, 2017)
The purpose of this study was to examine the effects of cloth wrap (CW) and ankle tape (TAP) techniques on vertical jump performance in 29 Division I football players. There was a significant reduction in vertical jump performance for both the TAP (76.2 ± 1.3 cm; t28= 6.5, p < .0005) and CW (77.3 ± 1.3 cm; t28= 3.9, p = .001) conditions as compared with the control (78.4 ± 1.3 cm). The TAP group also had reduced vertical jump scores as compared with the CW group (t28= 4.9, p < .0005). Both prophylactic techniques resulted in decreased vertical jump capability with the TAP having a greater negative impact than the CW.